2017
DOI: 10.1002/lary.26528
|View full text |Cite
|
Sign up to set email alerts
|

WFS1 and GJB2 mutations in patients with bilateral low‐frequency sensorineural hearing loss

Abstract: 4. Laryngoscope, 127:E324-E329, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This is an indication of the urgent need to implement this GJB2 -p.R143W testing in patients with HI clinical practice in Ghana. The p.R143W mutation has also been reported in patients with HI in Japan (Zheng et al, 2015; Kasakura-Kimura et al, 2017), South Korea (Kim et al, 2016), and China (Luo et al, 2017). In addition, we report a variant previously described as Mayan: founder GJB2 nonsense mutation (p.W44*) in a Ghanaian family.…”
Section: Discussionmentioning
confidence: 91%
“…This is an indication of the urgent need to implement this GJB2 -p.R143W testing in patients with HI clinical practice in Ghana. The p.R143W mutation has also been reported in patients with HI in Japan (Zheng et al, 2015; Kasakura-Kimura et al, 2017), South Korea (Kim et al, 2016), and China (Luo et al, 2017). In addition, we report a variant previously described as Mayan: founder GJB2 nonsense mutation (p.W44*) in a Ghanaian family.…”
Section: Discussionmentioning
confidence: 91%
“…One of the two LMX1A variants identified in this study occurred de novo. Also, we identified de novo variants with a dominant effect to explain four of 67 cases for whom a genetic diagnosis was established by testing a deafness gene panel and Kasakura-Kimura et al ( 2017 ) identified de novo variants as the cause of dominantly inherited HI in two of 74 ‘solved’ cases (Kasakura-Kimura et al 2017 ; Zazo Seco et al 2015 ). Interestingly, also for retinitis pigmentosa that displays very high genetic heterogeneity as does HI, the underlying genetic defect was found to be a de novo variant in 3 of 28 individuals without family history of the disease (Neveling et al 2012 ).…”
Section: Discussionmentioning
confidence: 96%
“…Pathogenic variants of the WFS1 gene (OMIM:606210) may cause Wolfram syndrome, Wolfram-like syndrome, or autosomal dominant non-syndromic DFNA6/14/38 [ 31 , 32 , 33 , 34 , 35 ]. Wolframin (WFS1), encoded by WFS1 , is an endoglycosidase H-sensitive membrane glycoprotein localized in the endoplasmic reticulum that is involved in the regulation of intracellular calcium homeostasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine (50%) patients underwent bilateral implantation, one of whom received bilateral simultaneous implantation. The preoperative hearing threshold was 88.2 ± 14.5 (57.5-106.3) dBHL, and the CI-aided hearing threshold was 25.6 ± 4.1 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) dBHL. The median CAP and SIR scores at the latest follow-up were 7 (range, 5-7) and 5 (range, 2-5), respectively, indicating that these patients showed excellent outcomes.…”
Section: Outcomes In Ansd Patients With Biallelic Otof Variantsmentioning
confidence: 99%